Case report: ALK-positive histiocytosis presented as bilateral synchronous breast masses with long-term remission on crizotinib - Zhou, Yuhang; Hurtado-Castillo, Marisabel; Pandey, Om (Frontiers in Medicine, 2023)
ALK-positive histiocytosis (APH) is a rare type of histiocytic neoplasm with characteristic ALK (Anaplastic Lymphoma Kinase) gene translocation and fusion, with only 27 reported cases in the literature. In this study, we report the first case of synchronous bilateral breast involvement of ALK-positive histiocytosis on initial presentation in a 46-year-old Hispanic woman. APH was diagnosed by the confirmation of clonal histiocyte proliferation with ALK overexpression on IHC and the presence of KIF5B-ALK gene fusion from her breast and lung biopsies. The patient in our study is currently under complete and long-term remission with crizotinib treatment (an ALK inhibitor). This report expands on the clinical manifestation of APH, emphasizes the importance of ALK detection in histiocytic diseases, and provides the efficacy and long-term prognosis of the ALK inhibitor therapy for APH.